Inhibitory Effect of Eslicarbazepine Acetate and S-Licarbazepine on Nav1.5 Channels - Leslie, Theresa K.; Brückner, Lotte; Chawla, Sangeeta; Brackenbury, William J. (Frontiers in Pharmacology, 2020)
Eslicarbazepine acetate (ESL) is a dibenzazepine anticonvulsant approved as adjunctive treatment for partial-onset epileptic seizures. Following first pass hydrolysis of ESL, S-licarbazepine (S-Lic) represents around 95 % of circulating active metabolites. S-Lic is the main enantiomer responsible for anticonvulsant activity and this is proposed to be through the blockade of voltage-gated Na+ channels (VGSCs). ESL and S-Lic both have a voltage-dependent inhibitory effect on the Na+ current in N1E-115 neuroblastoma cells expressing neuronal VGSC subtypes including Nav1.1, Nav1.2, Nav1.3, Nav1.6 and Nav1.7. ESL has not been associated with cardiotoxicity in healthy volunteers, although a prolongation of the electrocardiographic PR interval has been observed, suggesting that ESL may also inhibit cardiac Nav1.5 isoform. However, this has not previously been studied. Here, we investigated the electrophysiological effects of ESL and S-Lic on Nav1.5 using whole-cell patch clamp recording. We interrogated two model systems: (1) MDA-MB-231 metastatic breast carcinoma cells, which endogenously express the ‘neonatal’ Nav1.5 splice variant, and (2) HEK-293 cells stably over-expressing the ‘adult’ Nav1.5 splice variant. We show that both ESL and S-Lic inhibit transient and persistent Na+ current, hyperpolarise the voltage-dependence of fast inactivation, and slow the recovery from channel inactivation. These findings highlight, for the first time, the potent inhibitory effects of ESL and S-Lic on the Nav1.5 isoform, suggesting a possible explanation for the prolonged PR interval observed in patients on ESL treatment. Given that numerous cancer cells have also been shown to express Nav1.5, and that VGSCs potentiate invasion and metastasis, this study also paves the way for future investigations into ESL and S-Lic as potential invasion inhibitors.